2015
DOI: 10.1021/acs.macromol.5b00401
|View full text |Cite
|
Sign up to set email alerts
|

Multiresponsive Star-Graft Quarterpolymer Monolayers

Abstract: Multifunctional star-graft quarterpolymers PS n [P2VPb-(PAA-g-PNIPAM)] n with two different arm types, shorter PS arms and longer P2VP-b-PAA block copolymer arms with grafted PNIPAM chains, were studied in terms of their ability to form micellar structures at the air/water and air/solid interfaces. Because of the pH-dependent ionization of P2VP and PAA blocks, as well as thermoresponsiveness of PNIPAM chains, these multifunctional stars have multiple responsive properties to pH, temperature, and ionic strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 48 publications
0
67
0
Order By: Relevance
“…Insightful discussion of thiol-ene reaction for polymer-polymer conjugation has been provided in the reported studies. 46,[61][62][63][64] It is now accepted that the thiol-ene reaction is far from being satisfactory to be considered as a click reaction. Based on several intricate studies reported in the literature, reaction conditions for thiol-ene reaction have been suggested under which the reaction is (4) Photoinitiator whose generated radicals are capable of only abstracting proton from thiol (5) Higher ratio of thiol to photoinitiator and (6) Longer reaction time.…”
Section: Kinetics Of Rop Of E-caprolactone Using 3 Andmentioning
confidence: 99%
“…Insightful discussion of thiol-ene reaction for polymer-polymer conjugation has been provided in the reported studies. 46,[61][62][63][64] It is now accepted that the thiol-ene reaction is far from being satisfactory to be considered as a click reaction. Based on several intricate studies reported in the literature, reaction conditions for thiol-ene reaction have been suggested under which the reaction is (4) Photoinitiator whose generated radicals are capable of only abstracting proton from thiol (5) Higher ratio of thiol to photoinitiator and (6) Longer reaction time.…”
Section: Kinetics Of Rop Of E-caprolactone Using 3 Andmentioning
confidence: 99%
“…Tsukruk et al prepared a star‐graft quarterpolymer PS n [P2VP‐ b ‐(PAA‐ g ‐PNIPAM)] n (PS: polystyrene, P2VP: poly(2‐vinylpyridine)), which was responsive to pH, temperature, and ionic strength due to the presence of ampholytic P2VP‐ b ‐PAA arms and grafted PNIPAM blocks. The star block copolymer conformation and micellar aggregation were strongly dependent on the intramolecular interactions between different blocks and spatial distribution of the arms, which could be controlled by the external stimuli 132…”
Section: Multi‐stimuli‐responsive Particlesmentioning
confidence: 99%
“…Themechanism for the pH controlled permeability of the (TA/SGQP) 6 microcapsules is acombination of changes in the conformation of the SGQP and the hydrogen bonding interactions between TA and SGQP (Figure 2g). [29] At al ow pH condition (pH 3), the P2VP blocks are highly charged and extended, the grafted PNIPAM chains interact with the PA A block via hydrogen bonding,s ot hat the terminal block are collapsed. Thefully extended inner block as well as the loose interaction between collapsed arm ends with TA gives the microcapsules high permeability.I nc ontrast, when pH is increased to 7, the inner P2VP blocks are neutral and hydrophobic,a nd tend to collapse instead.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[28] TheS GQP PS n [P2VP-b-(PAA-g-PNIPAM)] n (PS:p olystyrene,P 2VP:p oly(2-vinylpyridine), PA A: poly-(acrylic acid)) contain two classes of arms,o ne is as horter hydrophobic PS arm, the other is apHresponsive hydrophilic P2VP-b-PAA block copolymer arm with grafted PNIPAM chains on the PA Ablock ( Figure 1b;Supporting Information, Tables S1, S2). Thec enter of the SGQP consists of ah ydrophobic polydivinylbenzene (PDVB) core and short PS chains, [29] which means the SGQP have the potential to encapsulate hydrophobic molecules in the core.T he grafting of poly(N-isopropylacrylamide) (PNIPAM) chains on the corona effectively shields the charges in the inner blocks, which can significantly extend their in vivo circulation for biomedical applications. [30] TheS GQP precursors were synthesized via ao ne-pot/ four-step sequential "living" anionic polymerization procedure (an extended "in-out" method), which was described in detail elsewhere.…”
mentioning
confidence: 99%
See 1 more Smart Citation